Psychological characteristics of school-leavers’ hardiness at their professional self-determination - Ingrida Baranauskienė; Liudmyla Serdiuk; Olena Chykhantsova (Social Welfare: Interdisciplinary Approach)
The article discusses the personal qualities of school-leavers that determine their hardiness at the stage of professional self-determination. It analyzes contemporary theoretical approaches to defining of the essence of the ‘hardiness’ concept. The factors are revealed that contribute to personal hardiness formation in the situation of professional choice. The article determines that hardiness components are related to the parameters of effective self-realization and personal subjective quality of life and hardiness is a key personality formation that mediates stress factor influence on psychological well-being and success in activities